An exploratory study of context-based mobile solutions for elderly people / Norsyamimi Abu Bakar - Abu Bakar, Norsyamimi (2010)
Mobile devices have become essential part of personal and business life crosses all age and gender boundaries. A tremendous increase in the usage of mobile devices can potentially play a significant role in assisting elderly people in many ways especially interms of maintaining social relationship, providing sense of safety, and accessibility. However, this senior citizen seems to be neglected user group in the design of mobile devices and services. Hence, this study attempts to explore context-based mobile solutions that are suitable for elderly people. In order to achieve the aim of the study, we used a survey instrument to gather data from elderly aged 50 to 75 years old that focuses only one target community which is in Bintong area at Kangar, Perlis. The results of our study indicate that elderly people are interested in using mobile phones and services, but these services need to deliver real value for them. For future studies, there would be a research that investigates deeply in user-centered design in a better understanding on adoption and the use of mobile devices and services for elderly people.